Proculus, giant latin-american passalids: revision, phylogeny and biogeography - Schuster, Jack C.; Cano, Enio B.; Reyes, Pedro (Instituto de Ecología, A.C., 2022)
The genus and its five known species are redescribed and P. jicaquei sp. nov. is described. Synonymies include P. beckeri Zang, 1905 with P. opacipennis (Thompson, 1857) (new synonymy), P. mandibularis Casey, 1914 with P. burmeisteri Kuwert, 1891 (new synonymy), P. magister Casey, 1897 with P. mniszechi Kaup, 1868 (new synonymy), P. densipennis Casey, 1914 with P. opacipennis (Thompson, 1857) (new synonymy), and P. kraatzi Kuwert, 1898 with P. mniszechi Kaup, 1868 (new synonymy). We include a phylogenetic analysis, keys for larvae and adults, and biogeographic information for each species. The genus occurs from Mexico to Colombia. Proculus mniszechi is parapatric with P. burmeisteri and partially sympatric with P. opacipennis in Sierra de las Minas, Sierra de Santa Cruz and Cuchumatan Mountains; P. mniszechi occurs in a type of cloud forest above 1500 m altitude, whereas P. opacipennis occurs in another cloud forest type below 1500 m. Proculus opacipennis has a similar relation with P. opacus Kuwert 1891 in the Cuchumatan Mountains, where P. opacus apparently replaces P. mniszechi. Proculus goryi (Melly, 1833) occurs in the volcanic chain of the Pacific coast of Guatemala and Chiapas, Mexico. Proculus jicaquei sp. nov. is known only from the mountains northwest of Yoro, Honduras. Phylogenetic hypothesis shows that P. jicaquei is most closely to P. goryi, these two taxa form a sister clade to all other Proculus species. Proculus mniszechi and P. burmeisteri are sister taxa, as are P. opacus and P. opacipennis.